Analisis Perbedaan Persepsi terhadap Kode Etik Akuntan Antara Akuntan Publik dan Akuntan Pemerintah - Tri Astuti; - Khanifah (Universitas Wahid Hasyim, 2006)
The role accountants in providing financial information is vital. The parties outside the company are relyingon the relevance and reliability of information provided by accountants entrused of ethical conducts in their duties. To guarantee the personal quality, a moral arrangemen as a professional attitude and aptitude guidance that is called accountant’code of ethics. It is expected that the personal quality of each accountant, whether public or government accountants are equal. Therefore it is the aim of this paper to test the differing perception toward the code of ethics among public and government accountants.The method used to collect data is mail survey, with a total of 40 questions sent to both public and goverment accountants (BPKP) in Semarang. The different test results indicate the axixtence of a significant difference inperception among publicang government accountants upon the code of ethics, especially in the factors of ethics and ethical rules. This result is expected to become a consideration for accountants to understand their code of ethics.